PEMBIAYAAN PENDIDIKAN MADRASAH (Studi Kasus pada MI Arrosidiyah Sumberagung Rejotangan Tulungagung) - Suprihno, Suprihno (EDUKASI: Jurnal Pendidikan Islam, 2016)
Funding is one of necessary inputs in education; it is necessary in order to implement all policies and programs to achieve the goals of the school and the quality of education. Madrasah as Islamic education institutions provide a major contribution of education in Indonesia, but not all Islamic school gets adequate education costs from the government. This study aims to determine how education funding of Islamic education in the MI Arrosidiyah Sumberagung Rejotangan Tulungagung. This study used a qualitative approach. The study was conducted through the source data from informants and documents, through data collection techniques such as observation, interviews, and documentation, as well as using data analysis techniques of data reduction, data presentation, and verification. The results showed (1) Budgeting education plan in Madrasah RKAM, needs 2014 budget of 84.22 million rupiahs sourced from the BOS funds 71.92 million rupiahs, BPPDGS, 10.8 million rupiahs, and the public donation of 1.5 million rupiahs. (2) use of budgeting the biggest MI Arrosidiyah used for teacher salaries amounted to 63.60%, next to school facilities by 10.41%, and the smallest funding to increase the competence of teachers by 2.98%. The unit cost 338,870.98 rupiahs while the amount of student unit, cost per hour; 273.85 Rupiahs. (3) Accountable education funding is transparent to the school committee, fundraising and teachers, and to Kementerian Agama Kabupaten Tulungagung.